On the optimum spacing of stereoscopic imaging atmospheric Cherenkov telescopes - Hofmann, Werner; Hermann, G; Konopelko, A; Krawczynski, H; Köhler, C; Pühlhofer, Gerd; Aharonian, Felix A.; Akhperjanian, A. G; Aye, M; Barrio, J. A; Bernlöhr, Konrad; Beteta, J. J. G; et al. (Astroparticle physics, 2000)
For stereoscopic systems of imaging atmospheric Cherenkov telescopes a key parameter to optimize the sensitivity for VHE γ-ray point sources is the intertelescope spacing. Using pairs of telescopes of the HEGRA IACT system, the sensitivity of two-telescope stereo IACT systems is studied as a function of the telescope spacing, ranging from 70 to 140 m. Data taken during the 1997 outburst of Mrk 501 are used to evaluate both the detection rates before cuts, and the sensitivity for weak signals after cuts to optimize the significance of signals. Detection rates decrease by about 1/3 between the minimum and maximum spacings. The significance of signals is essentially independent of distance in the range investigated.